Does Smart Service Recovery Harm Customer Orientation - Carrilho, Mariana Girão (2024)
Carrilho, M. G., Wagner, R. L., Pinto, D. C., González, H., & Akdim, K. (2024). Does Smart Service Recovery Harm Customer Orientation: A Feeling Economy Perspective [abstract]. In Proceedings of the European Marketing Academy Article 119606 European Marketing Academy (EMAC). https://proceedings.emac-online.org/pdfs/A2024-119606.pdf --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the projects UIDB/04152/2020 and 2023.03729.BD, Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.